Customer perceived value towards convenience stores in Malaysia: The influence on customer satisfaction, loyalty & retention - Abdulrauf Animashaun; Tarila Iman Tunkarimu; Omkar Dastane (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2016)
Numerous researchers have centred their attention on Customer Perceived Value towards brands but only a few have focussed on CPV towards convenience stores. The main purpose of the research is to measure the CPV dimensions and identify which dimension infl uences customer satisfaction and as a result leads to customer loyalty and retention for convenience stores in Malaysia. Independent variables such as functional, conditional, social, emotional and economic values were taken into account; the number of 200 customers were sampled, using a blend of explanatory and descriptive research design and a quantitative research method. The reliability was measured ranging from (» =.560-.966) using Cronbach's alpha. The application of descriptive statistics and correlation analysis was intended to explain the relationship between the independent and dependent variables of the research, whereas the inferential statistics and linear regression were used to test the hypotheses; with a significance level p È 0/05 whereby the findings of the research showed that economic value has a high influence on customer satisfaction as well as loyalty and retention. However, based on the findings customers are highly influenced by the economic value they get from a convenience store. Among the realistic contributions are positioning value pricing, formulating a strategy that encourages convenience value, connects to customers' emotions during shopping and also creates a diverse approach that sets a convenience store apart from another. However, there is a need for future studies to extend the model of this research by adding other perceptions such as demographic features of the consumers.
Keywords: M31; M39; 650; Customer Perceived Value; customer satisfaction; customer loyalty and retention; convenience stores; Malaysian retail